On the importance of retail banking relationships - Puri, Manju; Rocholl, Jörg (Journal of Financial Economics, 2008)
We use proprietary data to analyze the importance of retail banking relationships to commercial banks and their depositors when banks underwrite securities. We find lead underwriters’ retail customers benefit as they demand and end up with significantly more of the highly underpriced issues. We find it is actual underpricing beyond that predicted by grey markets that drive the differential demand from the lead bank retail clientele, suggesting that banks pass on information about underpriced initial public offerings to their retail depositors. We analyze banks’ incentives for such behavior and find evidence of banks benefiting through retail cross-selling—both brokerage accounts and consumer loans increase significantly.